ALERGI KARENA MAKANAN TRANSGENIK DAN PENCEGAHANNYA - Yovita Harmiatun (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2014)
In the last decade, there are many kinds of transgenic food in the tradisional and super market in Indonesia for example soybean, peanut, corn, rice, fruits, and many kinds of its processed food. Transgenic food is food which its primarily material consist of transgenic organism (genetically modified organism by genetic engineering=GMO). Unfortunately, based on the study on human in other countries and on experimental animals in Indonesia, those transgenic foods caused allergic reaction in the consumer, because these genetically modified foods carry a risk of triggering life-threatening allergic reactions. The results of those studies supported by my observation on my family experiences that transgenic foods like soybean, peanut, corn, rice, fruits, and its processed foods have caused allergic reaction in the human body. Allergic reaction can affect the brain, and then the endocrine system, and finally giving impact to the immune system. The decrease of immune system has impact to the decrease of health, so that the person can easily be infected by infectious diseases. The allergy can be prevented by avoiding those triggering transgenic foods.